Combination of Power Equalizing Education Financing Model and Flat Grand Model (Efforts to Equalize Education in Indonesia) - Nurulita, Aprilia; Alfiyyatur Rohmaniyyah, Ummi; Shaleh; Bin Muhammad, Mutsanna (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Abstract. Education financing is a crucial aspect in the effort to achieve equity and improve the quality of education in Indonesia. In this modern era, Indonesian society is still facing difficulties in accessing education due to insufficient financial resources. This research seeks to find a suitable educational financing model to accelerate efforts to equalize education in Indonesia. This research is classified as descriptive qualitative with literature study as the data collection technique. The results of this study show that the government needs to take decisive action to address the educational gap in Indonesia caused by funding disparities. The combination of the Power Equalizing Model and the Flat Grant Model presents an innovative solution to address the educational gap between regions. This integrated approach combines the advantages of both models to create a more effective and equitable financing system. With proper implementation, this integrated model can become an effective effort in realizing quality and equitable education throughout Indonesia. However, it is important to understand that the success of this integrated model in supporting educational equity highly depends on the commitment and cooperation of all stakeholders. Keywords: education equity, education financing, flat grant model, power equalizing